1999
DOI: 10.2110/jsr.69.216
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the strontium distribution coefficient in calcite; an experimental study from 408 degrees to 2008 degrees C and application to natural diagenetic calcites

Abstract: The temperature dependence of Sr coprecipitation with calcite was determined experimentally in solutions with Sr/Ca ratios and ionic strengths closely resembling marine pore fluids. Aragoniteto-calcite and dolomite-to-calcite transformations were conducted over a temperature range from 40؇ to 200؇C. Temperature dependence of the distribution coefficient of strontium in calcite (D ) is significant. c Sr D in aragonite-to-calcite experiments varied from 0.046 at 40؇C to c Sr 0.068 at 200؇C. D in dolomite-to-calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 39 publications
(76 reference statements)
2
24
0
Order By: Relevance
“…In Prali marble, the analysis of coexisting and cogenetic calcite and dolomite shows that higher contents of Sr and Fe occur in CaCO 3 mineral phase, suggesting the higher distribution coefficient of Sr and Fe in calcite than in dolomite as also supported by previous authors studying the temperature dependence of the distribution coefficient of strontium in calcite and dolomite [37,38]. However, from the observation of diagrams in Figure 2, the random scattering of the points representative of calcite (empty symbols) and dolomite (black symbols) leads to the conclusion that the concentration of trace elements, in each variety of marble, does not depend primarily on the type of carbonate mineral phase.…”
Section: Trace Elements In Calcite and Dolomitesupporting
confidence: 75%
“…In Prali marble, the analysis of coexisting and cogenetic calcite and dolomite shows that higher contents of Sr and Fe occur in CaCO 3 mineral phase, suggesting the higher distribution coefficient of Sr and Fe in calcite than in dolomite as also supported by previous authors studying the temperature dependence of the distribution coefficient of strontium in calcite and dolomite [37,38]. However, from the observation of diagrams in Figure 2, the random scattering of the points representative of calcite (empty symbols) and dolomite (black symbols) leads to the conclusion that the concentration of trace elements, in each variety of marble, does not depend primarily on the type of carbonate mineral phase.…”
Section: Trace Elements In Calcite and Dolomitesupporting
confidence: 75%
“…This is nearly an order of magnitude greater than the temperature dependence of D Sr in calcite inferred from aragonite -calcite and dolomite -calcite transformation experiments (Malone and Baker, 1999). For calcification rate, the linear relationship in all species corresponds to a change in Sr/Ca ratios of 2.0% to 1.6% per 100 pg calcite/cell/day in the range of 100 to 1500 pg calcite/cell/day.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, Tang et al, 2012 studied the effect of salinity parallel to the effect of rate of precipitation and found that it has an insignificant effect on the D Sr values. Also for biogenic calcite and experimental transformation of aragonite to calcite a positive or insignificant T dependence was observed (Katz et al, 1972;Jacobson and Usdowski, 1976;Baker et al, 1982;Stoessell et al, 1987;Lea et al, 1999;Humphrey and Howell, 1999;Malone and Baker, 1999;Stoll et al, 2002a,b).…”
Section: Introductionmentioning
confidence: 95%
“…In addition, the Sr/Ca ratio measured in aragonite has been widely used in paleooceanographic studies to estimate past sea surface temperatures (SST) (e.g., Smith et al, 1979;Rosenthal et al, 1997;Gagan et al, 1998). This elemental ratio is also used to understand the composition of past seawater, to study the diagenetic reactions that involve carbonate sediments (e.g., Lorens, 1981;Baker et al, 1982;Mucci and Morse, 1983;Richter and Liang, 1993;Banner, 1995;Humphrey and Howell, 1999;Malone and Baker, 1999). The Sr/Ca ratio in biogenic calcite was also correlated to both nutrient level and growth rate (e.g., Weinbauer and Velimirov, 1995;Stoll and Schrag, 2000;Stoll et al, 2002a,b).…”
Section: Introductionmentioning
confidence: 99%